2008
DOI: 10.2217/17435889.3.5.637
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Scavenging Properties of ZrO 2 –CeO 2 Solid Solution Nanoparticles

Abstract: The antioxidant efficacy of CeO(2) nanoparticles can be enhanced by dissolving zirconium in the CeO(2) lattice. The Ce(x)Zr(1-x)O(2) nanoparticles act as an enhanced catalyst at room temperature that scavenges ROS. Increased efficacy will enable lower nanoparticle dosages to protect cells from ROS, thus increasing the therapeutic width of these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 25 publications
2
29
1
Order By: Relevance
“…37 High surface areas can also increase surface reactivity leading to catalytic activities that can be both beneficial and detrimental to cells. 15 The surface areas, as determined by BET, closely ranged between 71 and 118 m 2 /g and it appeared that the presence of HMT had no dramatic influence on surface area.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…37 High surface areas can also increase surface reactivity leading to catalytic activities that can be both beneficial and detrimental to cells. 15 The surface areas, as determined by BET, closely ranged between 71 and 118 m 2 /g and it appeared that the presence of HMT had no dramatic influence on surface area.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of HMT that remains on the surface of the nanoparticles was determined with differential scanning calorimetry and thermogravimetric analysis (DSC-TGA) using a TA Instruments SDT-Q600 (New Castle, DE), with open alumina pans under 100 mL/min air flow. Particle size analysis was also carried out by measuring the specific surface area (m 2 /g) using the Brunauer, Emmett, and Teller (BET) method with a Quantachrome Nova 4200e surface area analyzer (Boynton Beach, FL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Impurity-doping or supporting effects can adjust the chemical reactivity of nanomaterials through modification of the electronic structure. Tsai et al 635 synthesized a series of Ce x Zr 1−x O 2 nanoparticles at room temperature using the reverse micelle method. The ROSscavenging activity of Ce 0.7 Zr 0.3 O 2 nanoparticles could be enhanced 4-fold as compared to CeO 2 nanoparticles.…”
Section: Key Factors Influencing the Antioxidant Properties Of Nanoceriamentioning
confidence: 99%
“…The antioxidant properties of CeO 2 NPs are accomplished through its ability to switch from the 3+ to the 4+ valence state ( Hirst et al 2009 ). It has been shown that the antioxidant efficacy of CeO 2 NPs can be affected by incorporation of zirconium (Zr) in the CeO 2 lattice ( Tsai et al 2008 ). However, whilst research has been devoted since many years to elaborate on neuroprotective and potential anti-neurodegenerative effects of CeO 2 ( Singh et al, 2007 ), adverse effects on the brain should also be considered for this type of nanoparticles as indicated e.g.…”
Section: Introductionmentioning
confidence: 99%